Ultra-processed food consumption and quality of life: a cross-sectional study in Iranian women - Hosseininasab, Dorsa; Shiraseb, Farideh; Bahrampour, Niki; da Silva, Alessandra; Hajinasab, Mohammad Mahdi; Bressan, Josefina; Mirzaei, Khadijeh (Frontiers in Public Health, 2024)
Background Ultra-processed foods (UPFs) have been associated with a higher intake of added sugars, sodium, and unhealthy fats; however, the relationship between UPFs and quality of life (QoL) is not well understood. Methods The present cross-sectional study included 193 Iranian women aged 18–48 years with a body mass index (BMI) of ≥25 kg/m2. UPFs were identified using the NOVA classification. QoL was evaluated using the SF-36 questionnaire. Anthropometric measurements and body composition were assessed using an appropriate method. Results The mean BMI and fat-free mass (FFM) of the subjects were 30.90 kg/m2 and 46.69 kg, respectively. At first, a significant difference was observed in the height of women across tertiles of UPF consumption. The mean score of the total QoL scale was 66.90. Women who were in the tertile 3 of UPFs intake had 23.59 units lower the scale of limitation in physical capabilities and activity (score of role-physical) (β = −23.59, 95% CI: −37.77–9.40, p = 0.001). Among those with the highest adherence to UPF intake, there was an 8.76 unit reduction in addressing feelings of energy and fatigue (vitality domain) in model 2 (β = −8.76, 95% CI: −16.42–1.11, p = 0.02). Finally, a reduction of 15.78 units was observed in the mental health scale, specifically in the mental states of anxiety and depression, among participants in the third tertile of UPF intake (β = −15.78, 95% CI: −24.11–7.45, p < 0.001). Conclusion Increased UPF consumption was associated with lower QoL in Iranian women. Further studies are needed to confirm these findings and develop effective strategies to promote healthy food choices.